Student ownership in the band classroom: assessing student understanding and increasing student buy-in - Whitaker, Brayden (My University, 2025)
In this project, I developed techniques and rehearsal strategies that give students more ownership and musical decision-making opportunities in the middle school and high school band setting. When students are able to make musical decisions and effectively lead their peers in music making experiences, it shows a competent understanding of musicality. It also enhances the cohesive atmosphere of the music classroom, giving the students a bigger stake in the learning occurring. Overall, these techniques have proven to be effective and a useful form of informal assessment during daily lesson planning. Students have been more engaged during lessons and have shown more buy-in to the rehearsal process. The experiences I have had during my Master’s degree program have helped me become a better teacher by exposing me to different philosophies of music education, which in turn has helped me form my own philosophies that inspire my daily teaching. One such self-developed philosophy, which inspired this project, is that the music classroom is a collaborative experience between the teacher and the students. The students have an equal say in the music education experience, and we as teachers need to make sure we plan for that and give our students a chance to take ownership and express their thoughts and feelings. Another development in my teaching due to my Master’s program experience would be an increase in my understanding of pedagogical aspects of music education. For example, I now have a better understanding of what makes quality literature and what aspects of that literature I can look for to address the needs of the ensembles I teach. I have also learned new rehearsal techniques that make me a more effective, more engaging teacher in the classroom.
Keywords: Student ownership; Rehearsal strategy